2001
DOI: 10.1046/j.1365-2834.2001.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress in nursing: a review of the literature

Abstract: The management and reduction of occupational stress are recognized as key factors in promoting employee well-being. Nursing is one of the many disciplines contributing to a huge body of research into the causes and effect of the ill-defined phenomenon of occupational stress. This literature review considers the ontological contribution of a number of disciplines to a growing body of knowledge on the subject of stress. The paper examines the complex issue of stress management, highlighting the impact of organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 16 publications
6
124
0
11
Order By: Relevance
“…Stress is a difficult concept to define precisely (Patel, 1996;Clegg, 2001;Keil, 2004), primarily as a result of the abundance of different disciplines with different perspectives on this subject (Le Blanc et al, 2000in Chmiel, 2000. Stringer is the Latin term for stress, which means to "draw tight" (Arnold et al, 1998, p.422).…”
Section: Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Stress is a difficult concept to define precisely (Patel, 1996;Clegg, 2001;Keil, 2004), primarily as a result of the abundance of different disciplines with different perspectives on this subject (Le Blanc et al, 2000in Chmiel, 2000. Stringer is the Latin term for stress, which means to "draw tight" (Arnold et al, 1998, p.422).…”
Section: Stressmentioning
confidence: 99%
“…However the consequences of stress in the working environment are considerable and include poor job satisfaction (McGowan, 2001) an association with high turnover (McCarthy et al, 2002) and impeded learning (Gaberson and Oermann, 1999). Therefore quantitative results with tested hypotheses to support the qualitative findings are necessary (Clegg, 2001). …”
Section: Philosophical Underpinnings For the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical supervision may be one strategy to protect health care workers against burnout (Livni et al, 2012;Queensland Health, 2009) as it has been suggested that increasing job resources such as professional support, mediates levels of burnout (Alkorashy & Baddar, 2016;Demerouti, Bakker, Nachreiner, & Schaufeli, 2001 It may be that clinical supervision can shield workers from burnout however there has been limited evidence to support these claims (Clegg, 2001;Koivu et al, 2012b), with varied and equivocal findings (Collins, 2008;Kim & Lee, 2009;Tilley & Chambers, 2003).…”
Section: Effectiveness Of Clinical Supervision and Burnoutmentioning
confidence: 99%